(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The present study aimed to identify the effectiveness of the counseling program among retirees in the ambitious development and Psychological resilience, study was applied to retirees in Karak governorate in the second half of the year 2015-2016, researcher followed the experimental method, and study sample consisted of 20 retired randomly selected were divided randomly into experimental groups and the control group equal footing. , was developed ambitious scale and the scale of flexibility, and build a counseling program for the development of ambition and flexibility where indicative Program of fifteen counseling session is, each of which lasts 60 minutes, the study results to the members of the experimental group who are retirees have fared in the level of ambition and flexibility compared to the control group who did not they have got better, also found that there were no statistically significant differences at (α = 0.05) between the mean scores of the experimental group in the two measurements dimensional and iterative ambitious psychological resilience scale, which indicates that the members of the experimental group had maintained after follow-up to their level for a period of two months, the study came up with some recommendations, including the use of the program in improving the developmental realistic ambition and flexibility among retired military.